Success Rate of Direct Hydroponic Cultivation Counseling and Training to Increase Mothers' Knowledge in Sambirejo Village Regarding Nutritional Fulfillment for Infants - Widya Yustika; Humairah Medina Liza Lubis; Nurcahaya Sinaga (International Journal of Health and Pharmaceutical (IJHP), 2026)
Hydroponic cultivation is increasingly relevant as a solution for household food security amidst limited land and a high prevalence of stunting in Indonesia. This study aims to measure the success rate of direct hydroponic counseling and training on improving the knowledge of mothers in Sambirejo Village regarding infant nutrition. Using a descriptive qualitative approach, the population was mothers with babies in the village with a sample of 20 people via purposive sampling. Instruments included pre-post test questionnaires and observations, analyzed by thematic data reduction and One-Way ANOVA. The results showed a significant increase in knowledge from an average score of 1.8 to 2.7 (p<0.05), the good category increased from 25% to 80%. It was concluded that the intervention was effective in improving understanding of infant nutrition through hydroponics, and integration into integrated health posts (Posyandu) was recommended.